COMMUNICATIVE INTERACTION AS A COMPONENT OF PROFESSIONAL SKILLS OF THE FUTURE TEACHER OF TECHNOLOGY (Pedagogy of Higher and Secondary Education, 2008)
The article is dedicated to the problem of forming the professionally significant communicative skills of would-be Handicraft teachers in the conditions of the introduction the educational field “Technology ”.